Ulm Aesthetics. (29th September 2019) - Holt, Matthew
Abstract: In order to contribute to the widening and enriching of the notion of aesthetics as it applies to design and so to the historian's task in this field, this essay examines the theories of aesthetics promulgated at the Hochschule für Gestaltung at Ulm (1953–1968), still a much-understudied institution. In particular, it will investigate the confluence at that school of semiotics and semantics, information aesthetics, and experimental aesthetics. It looks at the break Ulm made with its predecessor, the Bauhaus, on the role of art and aesthetics in design. That break is seen as result of the HfG's re-evaluation of the profile and substance of industrial design, a re-evaluation itself contingent on an updated understanding of the contemporary 'environment' ( Umwelt ). The article also examines the key aesthetic theories of the figures who passed through Ulm and shaped its curriculum in order to establish the influence of those figures on the wider history of design.